Chemical composition, fermentative losses, and microbial counts of total mixed ration silages inoculated with different Lactobacillus species. (3rd February 2019) - Restelatto, Rasiel; Novinski, Charles O; Pereira, Lucelia M; Silva, Eduardo P A; Volpi, Denise; Zopollatto, Maity; Schmidt, Patrick; Faciola, Antonio P
Abstract: The objective of this study was to evaluate the effects of Lactobacillus inoculants on fermentation, losses, and aerobic stability of a total mixed ration (TMR) silage. A TMR, formulated to meet the requirements of dairy cows producing 25 kg of milk/d, was applied with the following treatments prior to ensiling: 1) Control (CON), 2) Lactobacillus buchneri (10 5 cfu/g of fresh forage; LB), and 3) Lactobacillus plantarum (10 5 cfu/g of fresh forage; LP). TMR silages were ensiled for 15 and 60 d in silos equipped with an apparatus for determination of gravimetric DM, gas, and effluent losses. The experiment was performed in a complete randomized design with a 3 × 2 factorial arrangement of the treatments, with 5 replicates per treatment. Chemical changes, microbial counts, fermentation profile, and aerobic stability were measured after opening the silos. Data were submitted to ANOVA, and means were compared by Tukey and T -test and statistical significance was declared at P ≤ 0.05. After 15 d of ensiling, the inclusion of inoculant decreased NDF ( P < 0.05) and butyric acid concentrations ( P < 0.05) in TMR. LP had the lowest aerobic stability ( P < 0.05) and the greatest loss of DM ( P < 0.03). Ensiling for 60 d increased ammonia nitrogen (NH3 -N), lactic acid bacteria (LAB), aerobic stability, and concentrations of lactic and acetic acid ( P < 0.01) and lowered ( P < 0.02) total fermentation losses compared to 15 d across all treatments. After 60 d of ensiling, LP lowered pH to the greatest extent. Treatment had no effect on concentrations of DM, CP, ADF, ash, and EE, as well as in vitro DM digestibility. In conclusion, inoculants containing LP or LB did not improve fermentation profile, did not prolong the aerobic stability, nor reduced losses. Furthermore, the 15-d ensiling period was insufficient for adequate bacterial activity.